Application of Local Wheat Straw for Building Material and Products with Gypsum Binders - Akmalov M; Egamberdiev M.S; Majidov K.Kh (Genius Journals, 2023)
Dependencies describing the effect of crushed local wheat straw additives of different composition and specific surface area on the main physical-technical properties of construction gypsum have been defined. The effectiveness of adding crushed local wheat straw to construction gypsum increases with a decrease in the content of undrained clay from 14.1% to 9.5%. Gypsum-straw binder compositions have been developed, in which from 20 to 30% of construction gypsum is replaced by agricultural production waste, i.e., crushed wheat straw, without a significant decrease in physical and technical indicators
Keywords: Local crushed wheat straw; construction gypsum; heat straw gypsum mixture; steric restriction effect